Dispute Settlement And Compromise: The Need For An Uncompromising Stand - Choong, Yeow Choy (Journal of Malaysian and Comparative Law, 1998)
In this article, we will first examine some of the procedures in Malaysia and in other jurisdictions that encourage or allow parties to settle their disputes, both under the rules and outside the rules. Second, we will evaluate the effectiveness or otherwise of such procedures as a means of dispute settlement, and third, what reform, if necessary, may be introduced so as to ensure that the overriding objective of encouraging parties to compromise and settle their disputes without the need for a trial can be achieved.